Some Galumnidae (Acari, Oribatida) from Mexico - Sergey G. Ermilov (Persian Journal of Acarology)
A new species of the genus Pergalumna, P. rooensis sp. nov. is described from leaf litter in secondary semi-evergreen tropical forest in Mexico. The new species can be distinguished from the related species P. makarovae in the body size, the length of lamellar seta, the morphology of head of the bothridial seta, and the localization of notogastral lyrifissure im. Pergalumna silvatica Hammer, 1961 is recorded in Mexico for the first time.